PRESTIGE PERCEPTION ON TENGGERESE FARMERS TO POTATO FARMING IN NGADISARI VILLAGE, SUKAPURA DISTRICT, PROBOLINGGO REGENCY - Cahyo Nur Muhammad; Yuli Hariyati (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
The Tengger Tribe has a very strong integrity, so it affects all life activities including agriculture. The farming of this tribal community also greatly contributed to the supply of various horticultural crops, especially potatoes. The analysis of prestigious perception of Tenggerese farmers on potato farming in Ngadisari Village, Sukapura District, Probolinggo Regency is assessed from economic and socio-cultural aspects. The economic aspects is based on the income and financing of each commodity. The socio-cultural aspects are based on tribal life in seeing the development of agricultural businesses. The study was conducted with a descriptive analysis method. Respondents were taken as many as 30 people using the Snowball Sampling technique at Tenggerese farmers in Ngadisari Village. The research data were analyzed using descriptive analysis with a percentage of statements and farm analysis. The results showed (1) the existence of a prestigious perception with a percentage of 77% or 22/30 respondents stated that there was a prestigious perception of potato farming, (2) the economic aspect was assessed from the income per season of potato - leek intercropping (Rp. 64,516,695.60) > monoculture leek farming (Rp. 36,176,637.62) and potato farming (Rp. 36,960,001.11) > cabbage farming (Rp. 7,852,261.67), while the highest annual income is Rp. 172,246,681.49 and the lowest is Rp. 41,100,114.80 with the most prestigious business, namely potato and leek intercropping farming, (3) socio-cultural aspects are assessed from 8 socio-cultural elements.